The Five-Pillar Methodology: A Crucial Approach for a Successful Community Service Project - Nunes, L, Dobashi; Nunes, E, Dobashi; Lima, E, Rodrigues de; Nunes, Ronaldo (Research Collaboration Community (Rescollacom), 2024)
The five-pillar methodology has been applied in the community service project Gonçalinho in Brazil. This paper provides an extension and guidelines on how to apply our methodology as a foundation for a successful general community service project. Further advice regarding step-by-step approach will be provided. Behind the five-pillar methodology, a central point related to education as a foundation and lessons learned for life will be pointed out. Important aspects regarding challenges, strategies and future trends will be addressed. Finally, additional examples based on a real community service project will be highlighted.